Whole health and chiropractic: a commentary on historical roots, contemporary relevance, and future directions - Michele Maiers; Krista Ward; Michael Ramcharan; Logan Benjamin; Wren Burton; Zachary Cupler; Maruti Ram Gudavalli; Stephanie Halloran; Benjamin Holmes; Steven Huybrecht; Jeremy Jenkins; Claire D. Johnson; et al. (Chiropractic & Manual Therapies, 2026)
Abstract Background This commentary describes perspectives from workshop attendees at a North American educational conference on the chiropractic profession and its relationship with whole health. Whole Health is a paradigm shift within healthcare settings and funding agencies in the United States that utilizes a systems framework to transform healthcare. Whole health frameworks emphasize biopsychosocial well-being as defined by individuals, families, and communities, and leverages interprofessional, team-based approaches to promote well-being, disease prevention, and restoration of health. Main body Two separate, 60-minute workshop sessions were convened at the 2025 Association of Chiropractic Colleges Education Conference and Research Agenda Conference to discuss whole health and chiropractic. Attendees ( n = 105) included chiropractic academicians, researchers, practitioners, students, and organizational leaders from institutions largely based in the United States. Participants in 14 small groups discussed (1) ways the chiropractic profession aligns with whole health, and (2) how chiropractors can contribute to whole health in clinical practice and healthcare education. Notes taken by group scribes were collected from each workshop and generated 401 distinct comments. Thematic analysis with an inductive approach was used to group and define key topics that emerged from the data. Aspects of the chiropractic profession were described as historically being aligned with whole health for its foundational philosophy in innate healing and resilience, and for espousing person-centeredness and patient values. Themes describing the future contribution of chiropractic to whole health include evidence-based practice; communication and advocacy; integration into the broader healthcare system; and forward-facing education. There was overlap between past and future when considering holism; therapeutic alliance and patient empowerment for self-care; direct access; therapeutic conservatism; preventive health and lifestyle medicine; and longitudinal care. Conclusions The whole health paradigm presents an opportunity for chiropractors to be recognized contributors within multidisciplinary teams, using their expertise to aid chronic disease prevention, patient empowerment, and health care delivery innovations. Continued education and training, policy changes, and further research are required for the chiropractic profession to best serve patients and provide value within a whole health framework.